The Art of Distances Ethical Thinking in Twentieth-Century Literature - Stan, Corina (Northwestern University Press, 2018)
The Art of Distances identifies a preoccupation with interpersonal distance in a strand of 20th-century literature that includes the work of Orwell, Morand, Canetti, Murdoch, Benjamin, Ernaux, Grass, and Galgut. Specifically, Stan shows that these authors engage in philosophical meditations on the ethical question of how to live with others and how to find an ideal interpersonal distance at historical moments when there are no obviously agreed-upon social norms for ethical behavior. Bringing these authors into dialogue with philosophers such as Montaigne, Emerson, Nietzsche, Freud, Plessner, Heidegger, Nancy, Levinas, Sloterdijk, le Blanc, and Zaoui, Stan shows how the question of the right interpersonal distance became a fundamental one for these authors and explores what forms and genres they proposed in order to convey the complexity of this question. Albeit unknowingly, she suggests, they are engaged in fleshing out what Barthes called "a science, or perhaps an art, of distances."